DESIGNED WASTE MANAGEMENT SYSTEMS CONSTRUCTION AND DEMOLITION TO IMPROVE WASTE MANAGEMENT AND RECYCLING - Winata, Budi Harta; Manurung, Edison Hatoguan; Purwanto, Dwi (International Journal of Multidisciplinary Research and Literature, 2025)
This study aims to design a construction and demolition waste management system that can improve waste management and support material recycling in construction projects in Indonesia. Effective construction waste management is essential to reduce environmental negative impacts and improve material use efficiency in construction projects. Nonetheless, waste management in Indonesia remains constrained by insufficient infrastructure, limited awareness among construction industry stakeholders, and ineffective enforcement of current regulations. This research employs a qualitative methodology, incorporating literature reviews and interviews with industry practitioners to discern challenges and opportunities in construction waste management. The results show that technologies such as Building Information Modeling (BIM) can be essential in planning and managing waste. In contrast, implementing an occupational health and safety (OHS) management system that includes waste management will improve worker safety and project efficiency. This study suggests the importance of infrastructure development, increasing industry awareness, and strengthening regulations to improve waste management and support sustainable construction material recycling